Strategic feed formulation for relation of electrolytes to promote performance and prevent heat stress in broilers - Garcia Neto, Manoel [UNESP]; Gamba, Juliana Pereira [UNESP]; Rodrigues, M. M. [UNESP]; Faria Júnior, Max José de Araújo [UNESP]; Pinto, Marcos Franke [UNESP] (My University, 2011)
An experiment was conducted to evaluate the impact in relation of dietary electrolytes, based on changes in the balance Na+K-Cl (DEB) and the ratio (K+Cl)/Na (DER) on the performance and survival of broilers subjected to acute heat stress. A total of 1575 male broiler chicks from 1 to 46 d of age were allocated in a 5x3 factorial arrangement in a completely randomized design, totaling of 15 treatments with 3 replicates of 35 birds each. The treatments consisted of 5 diets with electrolyte balances, arising from combinations DEB/DER (150/3, 250/2, 250/3, 250/4 and 350/3), associated with different times of application or not of the acute heat stress on birds at 25 and 36 d old. All diets were cornsoybean meal based and formulated to meet or exceed NRC requirements. Chicks had ad libitum access to feed and water in floor pens with wood shavings as litter. It was possible to verify that a DEB of 250 mEq/kg and a DER very close to the 3:1 providing a more nutritionally adequate diet. There was, however, the impossibility of obtaining a more suitable electrolyte ratio for a very low DEB (150 mEq/kg) or very high (350 mEq/kg) and also, to a very narrow DER (2:1) or very wide (4:1), due to an unfavorable performance and survival rate of birds in these conditions electrolytes adjustments of K, Na and Cl. There was clear indication, with significant difference (P < 0.05), that the DER has the potential to improve the performance of broilers, since simultaneous adjustment made in DEB, even in conditions of acute stress. The results of performance and survival rate of this study also indicate clearly that DER could not replace the DEB, and vice versa, in practical diets for broilers. Therefore, it can be affirmed that the strategic formulation of the correct electrolyte balance for DEB and DER enhances the performance and is able to prevent the effect of heat stress in broiler chickens, leading to better performance and survival.
Keywords: Acute stress; Growth; Electrolytes; Performance; Requirements